The formulation of the Joint Plan of Action for the Reactivation of Agriculture in Latin America and the Caribbean: IICA Jamaica's preliminary recommendations. A discussion paper - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
140 páginas